Investigation of Neuronal and Adrenocortical Changes in Metyrapone- An 11 β-hydroxylase Inhibitor Induced Adrenal Insufficiency in Wistar Rats - Ganesh, Vakkalagadda Siva; Raghunathanaidu, Bharathi Doddla (International Journal of Pharmaceutical Investigation, 2025)
Background 11β-hydroxylase plays a key role in adrenal steroid hormone production, making it crucial in the development of adrenal insufficiency. Recently, there has been increasing interest in targeting this enzyme to induce adrenal insufficiency by using small molecule inhibitors. Materials and Methods Metyrapone was administered to Wistar rats in a dose-dependent manner, ranging from 100 to 200 mg/kg. Levels of cortisol, sodium, potassium, serotonin (5-HT), and Dopamine (DA) were measured. Results Metyrapone significantly reduced cortisol, sodium, and potassium levels, increased dopamine levels, and caused no notable change in serotonin. Conclusion The findings of this study suggest that metyrapone induces Adrenal Insufficiency in Wistar rats by inhibiting adrenal hormones and enzymes involved in steroidogenesis, as well as altering neurotransmitter levels in the brain. Histopathological analysis showed no significant damage or changes in the Paraventricular nucleus of the hypothalamus or the adrenal cortex.
Keywords: Adrenal Insufficiency (AI); Cortisol; Corticosterone; Aldosterone; Metyrapone (mety); Adrenocorticotropic Hormone (ACTH)